Article RETRACTED due to manipulation by the authors Islamic values and cultural identity in world cup football commentary - Alfurqan Alfurqan; Wuri Syaputri; Ardo Okilanda; Andi Indah Yulianti; Yulino Indra; Hastianah Hastianah; Mukhammad Isnaeni; Widyasari Widyasari; Rani Amrista (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study analyzed how football commentary during the World Cups of 2010, 2014, and 2018 serves as a reflection of cultural, religious, and community values within the Islamic country. The primary objective is to explore how these commentaries are used in Islamic teachings, cultural pride, and social unity into the fabric of sports narratives, and to assess the implications for Islamic education. The research employs a qualitative content analysis, focusing on football commentaries from YouTube impressions Muslim countries such as Saudi Arabia, Egypt, Indonesia, Turkey, and Morocco. The study examines how these commentaries are infused with values. The values are teamwork, respect, humility, and the connection of success with Islamic principles. The findings of this study found that football commentary is a potent tool for reinforcing national and religious identities, fostering a sense of unity, and promoting positive society values. For instance, commentaries from Saudi Arabia and Egypt highlight the link between football success and Islamic teachings, deepening the viewers' sense of cultural heritage. Indonesian and Turkish commentaries emphasize collective effort and social cohesion, mirroring broader community values. This research contributes to Islamic education by demonstrating how football can be an effective medium for imparting religious and moral values. By incorporating Islamic teachings into sports, educators and community leaders have the opportunity to engage younger generations in a way that is both relevant and meaningful. This approach not only helps to strengthen cultural identity but also provides a dynamic platform for promoting core Islamic values in a contemporary context.